2017
DOI: 10.1039/c7gc01017f
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous 1,3-dipolar cycloadditions promoted by copper nanoparticles in polydiacetylene micelles

Abstract: International audienceA novel colloidal catalyst was developed through the encapsulation of cuprous oxide nanoparticles in polydiacetylene micelles. The Cu-based catalyst was applied to the Huisgen cycloaddition reaction in fully aqueous medium. The process neither requires heating nor controlled atmosphere and the catalyst can be recycled in subsequent reactions without any loss of activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…But insofar as more typical Huisgen reactions are concerned, where copper catalysis is especially helpful in the Sharpless/Meldal sense, new nanoparticles have been reported that function as very efficient catalysts in water at room temperature. For example, Doris and co‐workers prepared a novel micellar array, where Cu 2 O NPs stabilized by oleic acid (from CuOAc, oleic acid, and trioctylamine + heat) were encapsulated into micelles composed of polydiacetylene (pDA) . A previously reported 3‐step protocol led to the pegylated amphiphiles that, dispersed in water and upon photolysis, polymerized the diyne units.…”
Section: New Cu Chemistry In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…But insofar as more typical Huisgen reactions are concerned, where copper catalysis is especially helpful in the Sharpless/Meldal sense, new nanoparticles have been reported that function as very efficient catalysts in water at room temperature. For example, Doris and co‐workers prepared a novel micellar array, where Cu 2 O NPs stabilized by oleic acid (from CuOAc, oleic acid, and trioctylamine + heat) were encapsulated into micelles composed of polydiacetylene (pDA) . A previously reported 3‐step protocol led to the pegylated amphiphiles that, dispersed in water and upon photolysis, polymerized the diyne units.…”
Section: New Cu Chemistry In Watermentioning
confidence: 99%
“…For example, Doris and coworkers prepared an ovel micellar array,w here Cu 2 ON Ps stabilized by oleic acid (from CuOAc, oleic acid, and trioctylamine + heat) were encapsulated into micelles composed of polydiacetylene (pDA). [48] Ap reviously reported 3-step protocol [49] led to the pegylated amphiphilest hat, dispersed in water and upon photolysis, polymerizedt he diyne units. The resulting enyne network serves as the core surrounding the copper.…”
Section: New Cu Chemistry In Watermentioning
confidence: 99%
“…XPS proved effective to identify and quantify the copper oxidation states. [18,45,46] XPS is a surface technique having a penetration depth of a few nm. Thus, XPS quantitatively pictures the oxidation state of the copper atoms/ions near the nanoparticle surface, which are the catalytically active sites, providing a basis to understand the catalyst activity.…”
Section: Eurjocmentioning
confidence: 99%
“…In this perspective, Cu(I) supported over styrene‐based polymeric beads, dimethylaminomethyl grafted polystyrene/divinylbenzene resin (Amberlyst 21), melamine and terephthalaldehyde have been explored for “click reaction” under heterogeneous conditions . Supported cuprous oxide nanoparticles also displayed good catalytic activity in alkyne‐azide click cycloaddition reaction under mild conditions …”
Section: Introductionmentioning
confidence: 99%
“…[17] Supported cuprous oxide nanoparticles also displayed good catalytic activity in alkyne-azide click cycloaddition reaction under mild conditions. [18] Herein, we report a new triazine functional hierarchical mesoporous organic polymer (HMOP) platform through the polymerization of cyanuric chloride and melamines with nanorod morphology possessing high BET surface area~1218 m 2 g À 1 and huge pore volume&γτ";6 mL g À 1 with dual micro/mesopore architectures. The present new Schiff base network serves as an efficient support due to abundance N sites for effective Cuchelation (Cu-HMOP) that provides a ligand-free catalyst system to be used in diverse organic catalysis.…”
Section: Introductionmentioning
confidence: 99%